Kualitas Sumber Daya Manusia dan Budaya Organisasi terhadap Optimalisasi Kinerja Karyawan BCA Percetakan Negara - Donna Winny Bethani; Hery Wihasnanto (Jurnal Manajemen Bisnis Krisnadwipayana, 2026)
This study was conducted to determine the effect of HR Quality and Organizational Culture on Employee Performance Optimization at PT. Bank Central Asia Percetakan Negara. This study uses a quantitative approach. The population in this study used all 30 employees of PT. Bank Central Asia Percetakan Negara. The sampling technique in this study used the census sample type. The data collection technique in this study used a questionnaire. The data analysis method used in this study is multiple linear regression and partial. The results of the study indicate that: 1) Human resource quality has a positive effect on employee performance; 2) Organizational culture has a positive effect on optimizing employee performance; and 3) Together, human resource quality and organizational culture have a positive effect on employee performance